Pengaruh Web Series Merek Soyjoy Terhadap Sikap Kepada Merek (Studi Eksperimen Pada Mahasiswa FE Universitas Tarumanagara) - Benedictus Erwin Prasetya; Cokki Cokki (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2019)
This study examines the effect of attitude toward the actor on attitude toward the brand through attitudes toward the product placement and attitude toward the film. The design of this research is experiment. The sampling technique using convenience sampling. Participants are 30 students of Faculty of Economics of Tarumanagara University in Jakarta. The treatment is web series by Soyjoy